2021
DOI: 10.1016/j.jinf.2021.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated COVID-19 in England: A national data linkage study

Abstract: Objectives : Nosocomial transmission was an important aspect of SARS-CoV-1 and MERS-CoV outbreaks. Healthcare-associated SARS-CoV-2 infection has been reported in single and multi-site hospital-based studies in England, but not nationally. Methods : Admission records for all hospitals in England were linked to SARS-CoV-2 national test data for the period 01/03/2020 to 31/08/2020. Case definitions were: community-onset community-acquired, first positive test <14 days pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…Hospital attendances (including admissions) was defined as any hospital attendance, including admissions and attendances at accident and emergency departments, 0–14 days after the first specimen date of the most recent infection episode. Hospital attendances (including admissions and diagnoses during hospital stay) was defined in the same way as hospital attendances (including admissions), but additionally included cases with a first specimen date occurring during their hospital stay (hospital-onset cases 27 ), to approximately match the definition used in NHS COVID-19 hospitalisation statistics. 28 The mortality outcome was defined as death occurring 0–28 days after the first positive specimen date of the most recent infection episode, again matching the definition used in routine UK government reporting.…”
Section: Methodsmentioning
confidence: 99%
“…Hospital attendances (including admissions) was defined as any hospital attendance, including admissions and attendances at accident and emergency departments, 0–14 days after the first specimen date of the most recent infection episode. Hospital attendances (including admissions and diagnoses during hospital stay) was defined in the same way as hospital attendances (including admissions), but additionally included cases with a first specimen date occurring during their hospital stay (hospital-onset cases 27 ), to approximately match the definition used in NHS COVID-19 hospitalisation statistics. 28 The mortality outcome was defined as death occurring 0–28 days after the first positive specimen date of the most recent infection episode, again matching the definition used in routine UK government reporting.…”
Section: Methodsmentioning
confidence: 99%
“…Nosocomial transmission and outbreaks of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have been frequently reported in various healthcare settings since the beginning of the pandemic [ 1 – 6 ]. Reported proportions of hospitalised Coronavirus Disease 2019 (COVID-19) patients suspected to have acquired SARS-CoV-2 in the hospitals vary widely, ranging from < 1% to 20% [ 7 10 ], and a national data linkage study in England estimated that 15% of laboratory-confirmed cases among hospital patients were healthcare-associated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…NHSE and PHE define a healthcare-associated case as any patient who tests positive for SARS-CoV-2 for the first time ≥8 days post admission to hospital. 6 , 18 Over the course of the first wave (1 March 2020 to 31 August 2020), one-third of all laboratory-confirmed cases in England were linked to a record of hospital attendance, 15.4% of which (∼5.3% of all confirmed cases) were suspected to be healthcare-associated, 19 although this figure is likely biased by the increased likelihood of a case being detected in hospital inpatients compared with those in the general community. From the analysis data from acute NHSE trusts over an extended time period from weeks 10–48 (1 March 2020 to 1 December 2020), the number of non-COVID-19 admissions per week ranged from 140 000–290 000 and the number of patients who developed a nosocomial infection in a single week peaked at ∼2000 ( Figure 2A–C ).…”
Section: Resultsmentioning
confidence: 99%